AKTIVITAS ANTIINFLAMASI EKSTRAK ETANOL 70% DAUN ASHITABA (Angelica keiskei) SECARA IN VIVO DENGAN PENGINDUKSI KARAGENAN - Haka As'ada; Yardi Saibi; Hendri Aldrat (Fakultas MIPA Universitas Tulang Bawang Lampung, 2018)
Ashitaba leaves (Angelica keiskei) or also known as tommorow's leaf is plant that known to have various health benefit, one of them is as an anti-inflammatory activity. The anti-inflammatory activity of ashitaba leaves has been known through in vitro assays. This study aims to determine the anti-inflammatory activity of 70% ethanol extract of ashitaba leaves through in vivo assay. Anti-inflammatory activity was performed on white male rat of Sprague dawley strain with induction method of edema on rat's foot using 1% carrageenan 0.2 ml. Rats were divided into 5 groups. The negative control group was given a 0.5% Na-CMC suspension, a positive control group was given sodium diclofenac suspension of 5.14 mg / kgBW, and the test group was given 70% ethanol extract of ashitaba leaves at a dose of 1000; 2000; and 4000 mg / kgBW suspended in 0.5% Na-CMC. The results showed that in that dose range the 70% ethanol extract of ashitaba leaves had anti-inflammatory activity that did not depend on the dose. Percentage of edema of 70% ethanol extract of ashitaba leaves dose 1000; 2000; 4000 mg / kgBB was significantly different with negative control (p ≤ 0,05) and had percentage of edema inhibition respectively 83,95%, 79,01%, and 80,25%. The results of this study showed that 70% ethanol extract of ashitaba leaves have anti-inflammatory activity. Keywords: Ashitaba, Angelica keiskei, tommorow's leaf, anti-inflammatory, carrageenan.